Pervasive versus situational childhood ADHD: latent classes and their clinical characteristics, based on parent and teacher ratings in a large longitudinal population sample. - Frick, Matilda A.; Hesser, Hugo; Sonuga-Barke, Edmund (European Child & Adolescent Psychiatry, 2024)
Attention-deficit/hyperactivity disorder (ADHD) diagnoses require symptoms to be present in two settings. Low levels of concordance between symptoms rated at home and school raise questions regarding this approach. The aim was to examine whether there are sub-groups with context-specific expressions of ADHD symptoms (i.e., at home or school only) with clinically significant problems sufficient to support a new diagnostic formulation. We applied latent class transition analysis to parent and teacher data (N = 10,476) from the Avon Longitudinal Study of Parents and Children (ALSPAC), collected at ages 8, 10, and 20 years. We examined the short-term stability of emergent classes and their childhood and adult-associated risk profiles. In addition to an Unaffected class (~ 45%), there was a Pervasive Combined class with elevated inattentive and hyperactive/impulsive symptoms at both home and school (~ 11%) and three classes with situational expressions; School Combined (~ 9%), Home Combined (~ 18%), and School Inattentive (~ 16%). Stability ranged from 0.27 to 0.78. The Pervasive Combined class was most symptomatic and impaired. School inattentive also displayed clinical symptom levels, whereas the School and Home Combined classes displayed subclinical levels. Different profiles regarding sex, cognition, conduct problems, and substance use emerged for the three situational classes. Distinct groupings of pervasive and situational ADHD expressions are identifiable in the general population. The isolation of a stable and burdensome Pervasive Combined class lends support to the current diagnostic approach. However, there are indications of situational expressions of ADHD with clinical symptom levels and associated difficulties.